On the Time-Varying Impact of China's Bilateral Political Relations on Its Trading Partners (1960-2022) - António Afonso; Valérie Mignon; Jamel Saadaoui (Center for Economic Studies and ifo Institute (CESifo), 2023)
We assess the impact of China's bilateral political relations with three main trading partners—the US, Germany, and the UK—on current account balances and exchange rates, over the 1960Q1-2022Q4 period. Relying on the lag-augmented VAR approach with time-varying Granger causality tests, we find that political relationships with China strongly matter in explaining the dynamics of current accounts and exchange rates. Such relationships cause the evolution of the exchange rate (except in the UK) and the current account; these causal links being time-varying for the US and the UK and robust over the entire period for Germany. These findings suggest that policymakers should account for bilateral political relationships to understand the global macroeconomic consequences of political tensions.
Keywords: C22; F51; Q41; 330; political relations; time-varying causality; lag-augmented vector autoregression; China